Differential protein expression and surface presentation generate high-frequency antigenic variation in Mycoplasma fermentans. - Theiss, P M (1993)
Mycoplasma fermentans, a wall-less prokaryote, is currently under investigation as a potential human pathogen. Recently, several surface lipoproteins have been shown to vary in expression between M. fermentans strains. Using specific antibodies to these lipoproteins, we investigated the extent and nature of antigenic variation within this species. Immunoscreening of type strain PG18 agar-grown colonies revealed marked heterogeneity in expression of distinct surface lipoproteins. Subsequent isolation and propagation of clonal isolates established isogenic lineages which displayed high-frequency (10(-2) to 10(-5) per generation) antigenic phase variation. [35S]cysteine-labeled protein profiles and Western immunoblots of phase-variant clones showed that several distinct integral membrane proteins undergo noncoordinate variation in expression. In addition to differential expression of epitope-bearing lipoproteins, differential accessibility of epitopes to antibodies was also documented as a mechanism generating surface phenotypic variation. Examination of one strain-variant antigen showed high-frequency phase variation to underlie previously observed antigenic differences between strains of this species. Thus, M. fermentans has a complex system capable of creating rapid changes in surface mosaics. This may profoundly affect mycoplasma-host interactions and may limit the methods by which populations of M. fermentans may be studied in vivo.